Peran Humas Kementerian Pariwisata dan Ekonomi Kreatif Dalam Mewujudkan Keterbukaan Informasi - Elpa Hermawan (JMK (Jurnal Manajemen dan Kewirausahaan), 2021)
Public relations have a very important role in carrying out the task of disseminating information to the public. The purposes of study was to obtain accurate information about the role of public relations in building information disclosure. The method used descriptive qualitative. The data collection process is the 2019 report document and literature review related to data analysis needs. Data analysis techniques are data reduction, data presentation, and drawing conclusions. Research data shows that public relations at the Ministry of Tourism have established public information services through Information and Documentation Management Officers, information centers, Electronic Post, information request and complaint services, and social media. This research has implications for the development of information disclosure service infrastructure for the public related to tourism in Indonesia.